The analysis of cohesive devices on efl learners’ argumentative text - Ary Dwi; Dona Rahayu Sugiharti; Nurma Dhona Handayani (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
Cohesive devices play an essential role in organizing ideas and constructing coherent argumentative texts, but many English as a Foreign Language (EFL) learners still experience difficulties in using them effectively. This study aims to identify the types of cohesive devices employed by EFL learners in argumentative writing and examine how the dominant cohesive devices reflect the way students construct meaning. Adopting a qualitative case study design, the research analyzed thirty-three argumentative texts written by sixth-semester students of the English Literature Study Program at Universitas 17 Agustus 1945 Surabaya. The data were analyzed using Halliday and Hasan’s cohesion framework, classifying cohesive devices into grammatical cohesion (reference, substitution, ellipsis, and conjunction) and lexical cohesion (repetition, synonymy, antonymy, hyponymy, meronymy, and collocation). The findings reveal that conjunction (50.9%) and reference (48.8%) were the dominant grammatical cohesive devices, whereas substitution (0.2%) and ellipsis (0.1%) were rarely used. In lexical cohesion, synonymy (32.4%) emerged as the most frequent device, followed by repetition (22.2%), collocation (16.8%), hyponymy (15.1%), antonymy (9.7%), and meronymy (3.8%). Furthermore, the dominance of conjunction and synonymy demonstrates that students primarily construct meaning by explicitly organizing logical relationships among ideas and reinforcing central arguments through lexical variation. These findings suggest that cohesive devices function not only as linguistic connectors but also as discourse resources that support coherent argument development in EFL argumentative text.